Self-medication practices among medical and nursing students in Tripura, India: a mixed-method study - Karmakar, Nabarun; Chakraborty, Tamal; Datta, Anjan; Nag, Kaushik; Datta, Shib Sekhar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: In developing countries like India, self-medication is a common practice because of costly clinical services and easy availability of medicine from pharmacies. There is an increase trend of self-medication among different health professional students apart from general people. This study aims to assess self-medication practice among medical and nursing students in Tripura, India. Methods: This cross-sectional study was conducted among undergraduate medical and nursing students of Tripura Medical College and Tripura College of Nursing, of Tripura for two months (January- February 2018). A pre-tested, semi-structured schedule was used to collect the required information. The collected data was entered in SPSS version 16.0, represented in proportions and p <0.05 was considered as statistically significant. Results: Overall 353 (88.3%) students of both courses practiced self-medication; prevalence was more among medical (91.5%) than nursing students (85%). Main source of information among medical students were books (90.2%) while 56.5% nursing students replied friends and/or seniors as primary source. Majority (53%) respondents took self-medication for headache (79.2% medical vs 72.4% nursing students) followed by fever (77.6% medical vs 52.4% nursing). Less than half of the respondents (48.5% medical vs 46.5% nursing students) believed that self-medication was harmful; maximum nursing students (71.5%) believed that self-medication is self-care as compare to medical students (56.5%). Conclusions: The study found wide practice of self-medication among students, inappropriate use of which may cause serious health hazards. Promoting education regarding self-medication and making healthcare system available can reduce self-medication practices substantially.